Evidence for Association between SH2B1 Gene Variants and Glycated Hemoglobin in Nondiabetic European American Young Adults: The Add Health Study. (September 2016) - Lange, Leslie A.; Graff, Mariaelisa; Lange, Ethan M.; Young, Kristin L.; Richardson, Andrea S.; Mohlke, Karen L.; North, Kari E; Harris, Kathleen M; Gordon‐Larsen, Penny
Summary: Glycated hemoglobin (HbA1c) is used to classify glycaemia and type 2 diabetes (T2D). Body mass index (BMI) is a predictor of HbA1c levels and T2D. We tested 43 established BMI and obesity loci for association with HbA1c in a nationally representative multiethnic sample of young adults from the National Longitudinal Study of Adolescent to Adult Health [Add Health: age 24–34 years; n = 5641 European Americans (EA); 1740 African Americans (AA); 1444 Hispanic Americans (HA)] without T2D, using two levels of covariate adjustment (Model 1: age, sex, smoking, and geographic region; Model 2: Model 1 covariates plus BMI). Bonferroni adjustment was made for 43 SNPs and we considered P < 0.0011 statistically significant. Means (SD) for HbA1c were 5.4% (0.3) in EA, 5.7% (0.4) in AA, and 5.5% (0.3) in HA. We observed significant evidence for association with HbA1c for two variants near SH2B1 in EA (rs4788102, P = 2.2 × 10 −4 ; rs7359397, P = 9.8 × 10 −4 ) for Model 1. Both results were attenuated after adjustment for BMI (rs4788102, P = 1.7 × 10 −3 ; rs7359397, P = 4.6 × 10 −3 ). No variant reached Bonferroni‐corrected significance in AA or HA. These results suggest that SH2B1 polymorphisms are associated with HbA1c, largely independent of BMI, in EA young adults.